2016
DOI: 10.1186/s40594-016-0042-3
|View full text |Cite
|
Sign up to set email alerts
|

Get a room: the role of classroom space in sustained implementation of studio style instruction

Abstract: Background: The characteristics of the classroom environment play an important role in shaping teaching practices and supporting research-based instructional strategies. One instructional strategy that has reimagined the classroom is the Student-Centered Active Learning Environment with Upside-Down Pedagogies (SCALE-UP). SCALE-UP uses studio-style instruction to facilitate student collaboration. Although there is significant interest in studio-style instruction, there is not much research-based guidance availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
36
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(40 citation statements)
references
References 22 publications
4
36
0
Order By: Relevance
“…So, it might be assumed that a similar environment would be beneficial for students solving physics problems with computers. However, it is also known that the arrangement of a classroom in regard to the physical layout has far reaching effects on classroom engagement and student to instructor rapport [5]. Only minimal research has been done on computational physics labs and the effects computers have on peer interactions [6,7].…”
Section: Theoretical Framing and Methodologymentioning
confidence: 99%
“…So, it might be assumed that a similar environment would be beneficial for students solving physics problems with computers. However, it is also known that the arrangement of a classroom in regard to the physical layout has far reaching effects on classroom engagement and student to instructor rapport [5]. Only minimal research has been done on computational physics labs and the effects computers have on peer interactions [6,7].…”
Section: Theoretical Framing and Methodologymentioning
confidence: 99%
“…Though classroom layout can be perceived as a barrier, it is not systematically tied to instructional practices that feature student-centered learning (Bathgate et al, 2019;Stains et al, 2018). Some have gone on to suggest instructors may be less likely to abandon newly adopted active learning-based instructional practices when the physical structure of their classroom is modified to specifically accommodate the teaching style (Knaub, Foote, Henderson, Dancy, & Beichner, 2016). When considering how students respond to classroom structure, Foote et al indicated that studio classrooms are associated with higher levels of active learning (2014).…”
Section: Environmental Factors' Relationship To Instructional Practicmentioning
confidence: 99%
“…The SCALE-UP classroom incorporates specially placed projectors and technology that allow for the display of student work. Whiteboards, which promote collaboration (Knaub, Foote, Henderson, Dancy, & Beichner, 2016), are available for students to work problems and display their findings to their peers and instructors. Each team has access to its own Internet-connected computer to complete interactive modules or electronic laboratory activities (Beichner, 2008(Beichner, , 2014Beichner et al, 2007;Gaffney et al, 2008).…”
Section: Student-centered Active Learning Environment With Upside-dowmentioning
confidence: 99%
“…It is well established that for the implementation and sustainment of active learning pedagogies, the thoughtful design of the physical classroom needs to be highly considered (Beichner et al, 2007;Cotner, Loper, Walker, & Brooks, 2013;Knaub et al, 2016;Whiteside, Brooks, & Walker, 2010). Discovery Learning occurs in a special environment, called the Chemistry Discovery Center, which has parallels to the SCALE-UP classroom (Beichner et al, 2007;Gaffney et al, 2008).…”
Section: Layout Of the Chemistry Discovery Centermentioning
confidence: 99%
See 1 more Smart Citation